Limited flexural control of fold-thrust belts on the Jurassic Sichuan Basin, South China - Wan, Neng; Liu, Shaofeng; Li, Xueyan; Zhang, Bo; Ren, Rong; Chen, Zhuxin (Frontiers in Earth Science, 2023)
The northern part of the Jurassic Sichuan Basin has long been thought of as a foreland basin in relation to the post-collisional compression along the northern margin of the Yangtze block. However, the exact coupling mechanism between mountain building and basin formation remains unclear. It remains uninvestigated how the fold-thrust belts have controlled basin subsidence. Flexural backstripping of the stratigraphic record, spanning from 201 to 149 Ma, along two cross sections that are perpendicular to the Micangshan fold-thrust belt and the Dabashan fold-thrust belt, respectively, reveals a limited flexural control of mountain loading on basin subsidence. Owing to the short-wavelength nature of 2 plate flexure, the basin-adjacent thrust belts exerted dominant control on basin subsidence only along its margin, failing to drive subsidence in the forebulge and backbulge regions. Flexural modeling results suggest that crustal thickening was relatively weak during the Early to Middle Jurassic. This was followed by a more rapid and intense phase of crustal growth in the Late Jurassic, possibly continuing into the earliest Early Cretaceous. Compared to the Micangshan region, the Dabashan region has experienced more intense compression during the Late Jurassic. Additionally, our results reveal spatial variations in plate rigidity along the northern margin of the Yangtze block, with greater plate stiffness in the Dabashan region. The presence of residual subsidence, an anomalous longwavelength subsidence component corrected for both basin-adjacent thrust loading and associated sediment loading, highlights the necessity for an additional driving mechanism for basin subsidence. This residual subsidence was likely dynamic subsidence induced by the flat subduction of the Paleo-Pacific plate (the Izanagi plate) beneath East Asia as the flat slab progressively migrated inland.